Pemanfaatan Pupuk Organik Dari Limbah Cangkang Telur Untuk Tanaman Pakcoy Dengan Menggunakan Sekam Bakar - Lutvi Ayu Andresta; Ade Momon (Jurnal Ilmiah Wahana Pendidikan, 2022)
The number of laying hens' egg production in 2022 amounts to around 500,000 eggs, causing an increase in egg shell waste. There are still many people, especially for residents of Kutamekar Village, Ciampel District, who lack knowledge about the many benefits of eggshell waste for agricultural land, it is the responsibility of students to carry out counseling and application. In KKN activities, students use to disseminate information about the use of organic fertilizer from eggshell waste for agricultural land, with one of the activities being the application of organic fertilizer from eggshell waste to pakcoy plants. After attending the counseling, the residents of Kutamekar village learned about the content and benefits of egg shells and they started collecting egg shells to help carry out KKN activities. This can help reduce regional waste, especially eggshell waste, which can be recycled into more useful and economical materials.